Perancangan Sistem Informasi Geografis Objek Wisata Sumatera Barat Berbasis Web - muhammad danial; Sularno (CV. ITTC INDONESIA, 2024)
West Sumatra is one of the cities in the province of West Sumatra which has great tourism potential, especially in cultural and historical tourism. Where in this city there are many tourist attractions. But in reality, information regarding this matter is still limited, especially for foreign tourists who are more familiar with Bali as Indonesia. One way to introduce tourism is by utilizing webGIS technology as the aim of this research is to produce a tourism webGIS for the city of West Sumatra which can be accessed via the internet. With webGIS, West Sumatra city tours can be displayed which are equipped with map location points and travel routes and can be accessed via an internet browser without the help of GIS processing software. The tours displayed are culinary tours, shopping tours,. Making webGIS using the gis mapping method by utilizing Google Maps API technology and the CodeIgniter Framework. With LBS, tourist location coordinates in the form of latitude and longitude originating from the Google Maps application can be easily entered into the webGIS code structure. This WebGIS was successfully accessed via an internet browser on both computer devices